The Impact of Extensive Reading Technique on The Student’s Vocabulary Mastery at The Eight Grade Of SMPN2 Kualuh Selatan - Tarigan, Fatin Nadifa; Damanik, Dea Lovita; Nurhalimah (Talenta Publisher, 2025)
The objective of this study is to determine whether there is an impact of the extensive reading techniques on the eighth grade students, vocabulary mastery at SMPN2 Kualuh Selatan. This study used a quasi-experimental design using a non-equivalent pretest-posttest design. The population of this study was all 125 students of grade VIII of SMPN2 Kualuh Selatan. The research sample was taken using a random sampling technique. The number of samples was 50 students. The findings showed that there was a significant increase in the vocabulary mastery of eighth grade students taught using the extensive reading technique. The results showed that the average of the experimental group was 77.5 and was included in the good category. The average of students taught to read using extensive reading techniques is 77.5, the average of students taught to read without using extensive reading techniques is 66.66. This can be seen from the final results of the t-test analysis which states that the t-count value is greater than t-table (7.2564>2.010).